2017
DOI: 10.1016/j.earscirev.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and opportunities of addressing particle size effects in sediment source fingerprinting: A review

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
152
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(154 citation statements)
references
References 167 publications
(244 reference statements)
1
152
1
Order By: Relevance
“…Any sediment source tracing study needs to make careful decisions about the particle size fraction used, because this decision can impact heavily on the comparability of source and sediment samples and the reliability of the apportionment results generated (Collins et al, ; Laceby et al, ). Dry sieving (using sieve apertures of 500, 300, 250, 212, 125, 75, and 63 μm) revealed that the <63‐μm fraction was the dominant fraction of the “drape” sediment samples.…”
Section: Methodsmentioning
confidence: 99%
“…Any sediment source tracing study needs to make careful decisions about the particle size fraction used, because this decision can impact heavily on the comparability of source and sediment samples and the reliability of the apportionment results generated (Collins et al, ; Laceby et al, ). Dry sieving (using sieve apertures of 500, 300, 250, 212, 125, 75, and 63 μm) revealed that the <63‐μm fraction was the dominant fraction of the “drape” sediment samples.…”
Section: Methodsmentioning
confidence: 99%
“…Rittner et al () argued that the Kunlun Mountains (Figure ) are the main source of the desert sediments, based mainly on detrital zircon U‐Pb ages and mineralogy. These contrasting interpretations can be attributed to specific grain size fractions having different source rocks (Laceby et al, ). Yang et al () demonstrated the homogeneity of the fine fraction (<53 μm) and the significant differentiation of the coarse fractions (>250 μm) for the entire desert.…”
Section: Introductionmentioning
confidence: 99%
“…For a comprehensive review of the current state of knowledge of the frequentist approach to tracer selection, readers are directed to the reviews by Collins et al (), Davis and Fox (), Haddadchi, Ryder, Evrard, and Olley (), Laceby et al (), Owens et al (), Smith, Karam, and Lennard (), and Walling ().…”
Section: Frequentist Approachmentioning
confidence: 99%